Species checklist for the tribe Vartini Zahniser & Dietrich, 2013 (Hemiptera: Cicadellidae: Deltocephalinae) from China, with description of a new species - Xing, Ji-Chun; Li, Zi-Zhong (Zootaxa, 2015)
An annotated checklist and generic key to the leafhopper tribe Vartini from China is provided. A new species Xenovarta falcata sp. nov. is described and illustrated, and a key is given to separate species of this genus from China. A map showing the geographic distribution of the new species is also provided. The type specimen of the new species is deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).